Rapid detection of viable Escherichia coli O157:H7 by antimicrobial incorporated multi-angle light scattering spectroscopy - León, Juan Carlos, author; Goodridge, Lawrence D., advisor; Bunning, Marisa, advisor; Nightingale, Kendra K., committee member (Colorado State University. Libraries, 2010)
Escherichia coli 0157:H7 continues to cause outbreaks of produce-associated foodborne illness. Contaminated water has been shown to be a vehicle for transfer of E. coli 0157:H7 to leafy greens during irrigation. Timely detection of this pathogen in irrigation water can prevent contamination of the final product. Current detection methods which are culture-based can be labor intensive and require several days to produce results. There is a need for development of rapid detection methods, which can detect E. coli 0157:H7 in irrigation water. These methods have to be sensitive, robust and ideally should be able to differentiate between viable and non-viable microorganisms. Multi-angle light scattering spectroscopy (MAES) is a powerful technique that has been applied to qualitatively and quantitatively distinguish internal structural changes in cells upon perturbation by chemical/biological agents. We hypothesized that combining bacteriophage (phage) infection, which occurs only in viable bacterial cells, with MAES would allow for detection of the target bacteria and distinguish between viable and nonviable bacterial cells. The objective o f this study was to use E. co//-specific bacteriophages in conjunction with immunomagnetic separation and MAES to develop an assay for rapid detection of viable E. coli 0157:H7 in irrigation water. We have termed this new method Antimicrobial Incorporated Multi-angle Light Scattering (ANIMALS) to highlight the combination of a specific antimicrobial agent (phages) with the multi-angle light scattering technique to form a sensitive, rapid and specific assay for detection of E. coli 0157;H7. E. coli 0157:H7 and Salmonella Typhimurium strains were diluted in lambda buffer to form concentrations of 10*^ to lO"^ CFU/ml and 10*, respectively. The samples were subjected to immunomagnetic separation (IMS) using E. coli 0157-specific IMS beads. Following IMS, the beads (and attached bacteria) were resuspended in 1 ml of tryptic soy broth (TSB) and one half (500 pi) of each sample was added to 10 mis of TSB that contained 1 ml of phage ARl (lO'** PFU/ml). The other half of the samples were added to TSB that did not contain phage AR l, but contained 1 ml of lambda buffer (to maintain constant volume), and these samples served as a reference. The samples were incubated at 37° C, with shaking, for 15 hours. Following incubation, 100 pi aliquots were removed from each sample, and separately assayed using a SpectraPoint light scattering spectrometer (Spectra Digital Corp., Toronto, Ontario, Canada). E. coli 0157:H7 was detected in 100% of pure culture samples in TSB containing various concentration (10*^ to 10^) of the bacterium within 15 hours. An algorithm was developed to evaluate the area under the curve of each spectra. When compared to the light scattering spectra of the non-phage treated reference, the spectra o f phage infected E. coli 0157:H7 cells differed markedly. In contrast, the spectra of samples that contained Salmonella Typhimurium and the negative controls (containing no cells) were almost identical, because phage ARl does not infect Salmonella Typhimurim and there was no growth in the negative control samples, respectively. Using this method, E. coli 0157:H7 could be detected following 15 hours of incubation in samples spiked at an initial concentration of 10** CFU/ml. The sensitivity and specificity of the ANIMALS assay was determined using environmental water samples. River water samples were artificially contaminated with a 3-strain cocktail of E. coli 0157:H7, followed by IMS and incubation in TSB supplemented with 20 mg/ml novobiocin at 42° C. MALS measurements were taken at 4, 6, 8 and 10 hours. The means and standard deviations of the ratios o f the differences between the test and reference spectra for the four concentrations (10‘^ to 10^ CFU/ml) o f E. coli 0157;H7 were analyzed as well as for negative controls (samples o f river water that were not inoculated with E. coli 0157:H7). One concentration (10^ CFU/ml) of E. coli 0157:H7 was detected consistently after only 6 hours of enrichment. E. coli 0157:1-17 was consistently detected at concentrations from 10‘ to 10^ CFU/ml in spiked river water within 8 hours. All concentrations (10° to 10^ CFU/ml) were detected after 10 hours of enrichment. The presence of the pathogen in positive river water samples was confirmed by using lateral flow devices specific for E. coli 0157:H7. The negative controls resulted in negative readings. Additionally, reservoir water samples were prepared similarly to river water samples and MALS measurements were taken at 4, 6, 8 and 10 hours. The test and reference spectra for the four concentrations (10° to 10^ CFU/ml) of E. coli 0157:H7 were analyzed as well as for negative controls (samples o f reservoir water that were not inoculated with E. coli 0157:H7). Similar results to experiments on river water were obtained with 10^ concentrations of E. coli 0157:H7 detected consistently at 6 hours. This demonstrated that the ANIMALS assay worked consistently across water samples with different physical and chemical characteristics. Regardless, E. coli 0157:H7 was consistently detected in 100% of concentrations (10 to 10 CFU/ml) within 8 hours even against background levels of bacteria as high as 10^ CFU/ml. Lateral flow devices specific for E. coli 0157:H7 confirmed the presence of the pathogen in positive reservoir water samples. The negative controls resulted in negative readings. These results demonstrate the ability of ANIMALS to rapidly and sensitively detect the presence and viability of E. coli 0157:H7 following phage infection. This method has the potential to allow for rapid detection o f viable E. coli 0157:H7 in irrigation water against a high background o f non-target microorganisms if coupled with selective enrichment.
Covers not scanned.
Keywords: Escherichia coli O157:H7; Spectrum analysis